Benchmarking of abdominal surgery: a study evaluating the HARM score in a European national cohort. Issue 4 (21st April 2020) - Helgeland, J; Skyrud, K; Lindahl, A K; Keller, D; Augestad, K M
Abstract: Background: Reliable, easily accessible metrics of surgical quality are currently lacking. The HARM (HospitAl length of stay, Readmission and Mortality) score is a composite measure that has been validated across diverse surgical cohorts. The aim of this study was to validate the HARM score in a national population of patients undergoing abdominal surgery. Methods: Data on all abdominal surgery in Norwegian hospitals from 2011 to 2017 were obtained from the Norwegian Patient Registry. Readmissions and 30-day postoperative complications as well as deaths in and out of hospital were evaluated. The HARM scoring algorithm was tested after adjustment by establishing a newly proposed length of stay score. The correlation between the HARM score and complications, as well as the ability of aggregated HARM scores to discriminate between hospitals, were analysed. Risk adjustment models were developed for nationwide hospital comparisons. Results: The data consisted of 407 113 primary operations on 295 999 patients in 85 hospitals. The HARM score was associated with complications and complication severity (Goodman–Kruskal γ value 0·59). Surgical specialty was the dominating variable for risk adjustment. Based on 1-year data, the risk-adjusted score classified 16 hospitals as low HARM score and 16 as high HARM score of the 53 hospitals that had at least 30 operations. Conclusion: The HARM score correlates with major outcomes and is associated with the presence and severity of complications. After risk adjustment, the HARM score discriminated strongly between hospitals in a European population of abdominal surgery. Graphical Abstract: The HARM score, calculated from length of stay, readmissions and postoperative mortality, was studied in a national gastrointestinal surgical population. It was found to be associated with complications and could differentiate between hospitals. benchmark in abdominal surgery